Plakat "Mut und Tat // Hans Sappeur als Stadtrat"
politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahlorganisation;Wahlkampf politischer Rahmen;politische Partei (allgemein);politische Partei (speziell);LdU politischer Rahmen;Wahlen und Abstimmungen;Wahl;Wahl der Exekutive